2016
DOI: 10.3109/11038128.2016.1152294
|View full text |Cite
|
Sign up to set email alerts
|

Perceived factors in return to work after acquired brain injury: A qualitative meta-synthesis

Abstract: The results of the meta-synthesis indicate that personal development is experienced as essential in order to return to work after an acquired brain injury, involving identification of each individual's strengths and weaknesses. These personal factors intersect with an emphasis of the employer providing a certain degree of facilitation in the workplace. All of these aspects will affect one's motivation to return to work and can therefore be crucial to succeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In addition, in this study, lack of awareness was not significantly related to the return to work, which again was in contrast with previous findings. 62,63 However, in accordance with our results, Hoofien et al 61 did not find any significant relationship between awareness of disorders and return to work in a group of patients with TBI.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in this study, lack of awareness was not significantly related to the return to work, which again was in contrast with previous findings. 62,63 However, in accordance with our results, Hoofien et al 61 did not find any significant relationship between awareness of disorders and return to work in a group of patients with TBI.…”
Section: Discussionsupporting
confidence: 90%
“…Participants in this study also discussed the long-term psychosocial impact of living with an ABI. The findings from this study are consistent with previous research which has found that there is limited service provision for ABI survivors in supporting social reintegration (Hofgren et al, 2010;Liaset and Loras, 2016). Those who are not able to successfully integrate back into the community through employment and other means have decreased self-esteem and feelings of loss of control (Gilworth, 2008) and are more likely to experience social isolation and deprivation (All Party Parliamentary Group for Acquired Brain Injury, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Within the discipline of occupational therapy, qualitative meta-synthesis and particularly meta-ethnography is growing in popularity (for example, see Classen et al., 2009; Fossey and Harvey, 2010; Frostad et al., 2016; Gibbs et al., 2015; Shamrock et al., 2016; York and Wiseman, 2012). Recent reviews using meta-ethnography illustrate the potential of the method to contribute to occupational therapy practice and research.…”
Section: Discussionmentioning
confidence: 99%
“…York and Wiseman (2012) included four studies in their meta-ethnography of gardening as an occupation, and developed a line of argument synthesis showing that the natural environment acted as stage on which people could develop their emotional, spiritual, cognitive and physical abilities. Frostad et al. (2016) used meta-ethnography to synthesise findings from 16 studies, and identified four key concepts as important for return to work after an acquired brain injury: empowerment, self-awareness, motivation and facilitation.…”
Section: Discussionmentioning
confidence: 99%